STANDAR PENGELOLAAN PENDIDIKAN MA BPII (BADAN PERGURUAN ISLAM INDONESIA) PAMBOANG DALAM PERSPEKTIF MANAJEMEN BERBASIS SEKOLAH DAN MANAJEMEN MUTU TERPADU - nurfitri nurfitri (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
The study aimed to reflect the implementation of the standard for management of education in a shool-based and integrated quality management perspective in MA BPII (Indonesian Islamic School) Pamboang. The study used a type of qualitative research with an approach to case studies. The object of this study was carried out in ma bpii (the Indonesian islamic school) Pamboang. Data collection techniques used observation, interviews, and documentation. The data sources in the study included the headmaster, curriculum section vice principal, students, publicists, sarpras, committee and students. The analysis techniques used in the study are data collecting, data reduction, data presentation, deduction. The triangulation used to test the validity of data is source triangulation.Research showed that the management of education in MA BPII Pamboang was established from the decision of the head of the school to manage education in MA BPII Pamboang, from the independence of the principal to take decisions in curriculum and student classes, the participation of all schoolchildren from the principal, teacher, and teacher. The education and education participants have a crucial share in all of the activities that are available in MA BPII Pamboang, where school management was conducted according to each other's ability, and the principal gives all schoolchildren an opportunity to make an opinion to improve the quality of education ma bpii pamboang. Integrated quality management in MA BPII (Indonesia islamic School) researcher found that it had not fully applied integrated quality management, as shown by studies that researcher had found only 5 integrated quality management principles from 8 existing ones.